Trans, trans-2,4-decadienal impairs vascular endothelial function by inducing oxidative/nitrative stress and apoptosis - Yuanyuan Hu; Fawen Yin; Zhenlong Yu; Yulin Peng; Guanhua Zhao; Zhongyuan Liu; Dayong Zhou; Xiaochi Ma; Fereidoon Shahidi; Beiwei Zhu (Redox Biology, 2020)
Aldehydes are implicated in the development of hypertension. Trans, trans-2,4-decadienal (tt-DDE), a dietary α,β-unsaturated aldehyde, is widespread in many food products. However, the role of tt-DDE in the pathophysiology of hypertension remains unknown. This study was designed to investigate whether tt-DDE consumption evokes hypertension and to explore the mechanisms underlying such a role. Sprague-Dawley rats were administered different concentrations of tt-DDE. After 28 days, blood pressure and endothelial function of mesenteric arteries were measured. Results showed that tt-DDE treatment significantly increased blood pressure and impaired endothelial function based on endothelium-dependent vasorelaxation and p-VASP levels. Mechanistically, tt-DDE induced oxidative/nitrative stress in the arteries of rats as evidenced by overproductions of superoxide and peroxynitrite, accompanied with increased expressions of iNOS and gp91phox. To further investigate the effects of tt-DDE on endothelial cells and underlying mechanisms, human umbilical vein endothelial cells (HUVECs) were treated with different concentrations of tt-DDE. tt-DDE induced oxidative/nitrative stress in HUVECs. Moreover, tt-DDE induced endothelial cells apoptosis through JNK-mediated signaling pathway. These results show, for the first time, that oral intake of tt-DDE elevates blood pressure and induces endothelial dysfunction in rats through oxidative/nitrative stress and JNK-mediated apoptosis signaling, indicating that excess ingestion of tt-DDE is a potential risk factor for endothelial dysfunction and hypertension.